Judge Frank Creede, Jr. Swears In Superior Court Judge Mario Olmos - Watkins, Howard::::::::: (1983)
Mary Louise Frampton holding Margaret Olmos and Judges Mario Olmos and Frank Creede, Jr. doing a toast Law Offices of Olmos and Frampton at 925 N St. #150, Fresno